ANALYSIS OF FACTORS INFLUENCING BARISTA INTEREST IN OPERATING A MODERN COFFEE SHOP IN MEDAN CITY, MEDAN PROVINCE NORTH SUMATRA - Ira Lisyani Tampubolon; Syahbudin; Endang Sari Simanullang (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
A barista is someone who is professional in preparing and serving various types of coffee drinks. Baristas usually work in modern cafes or coffee shops and they have special skills in operating espresso machines and understanding various coffee making techniques. Many baristas are interested in opening their own coffee shop business. This interest is usually based on passion for coffee, creativity, experience, family environment, education and capital. The aim of this research is to examine the factors that influence baristas' interest in modern coffee entrepreneurship in Medan City, North Sumatra Province. The research results show that educational factors and family environment do not show a real influence on the interest of baristas in starting a modern coffee shop entrepreneurship, while experience, capital and creativity show a real influence on the interest of baristas in starting a modern coffee shop in Medan City.